Systemic activation of Nrf2 pathway in Parkinson's disease. Issue 1 (4th November 2019) - Petrillo, Sara; Schirinzi, Tommaso; Di Lazzaro, Giulia; D'Amico, Jessica; Colona, Vito L.; Bertini, Enrico; Pierantozzi, Mariangela; Mari, Luisa; Mercuri, Nicola B.; Piemonte, Fiorella; Pisani, Antonio
Abstract: Background: Preclinical studies underlined the relevance of Nuclear factor erythroid 2‐related factor 2 (Nrf2) transcription factor pathway in the pathogenesis of Parkinson's disease (PD). Objective: The objective of this study was to explore Nrf2 pathway in vivo in PD, looking for novel disease biomarkers and therapeutic targets. Methods: The levels of Nrf2, the downstream effectors (NAD(P)H dehydrogenase [quinone] 1 (Nqo1) enzyme, glutathione metabolism enzymes Glutamate–cysteine ligase (GCL) and Glutathione Reductase (GR)), the upstream activators (redox state and mitochondrial dysfunction), and α‐synuclein oligomers were assessed in the blood leukocytes of PD patients comparatively to controls. Biochemical data were correlated to clinical parameters. Results: In PD, Nrf2 was highly transcribed and expressed as well as its target effectors. The mitochondrial complex I activity was reduced and the oxidized form of glutathione prevailed, disclosing the presence of pathway's activators. Also, α‐synuclein oligomers levels were increased. Nrf2 transcript and oligomers levels correlated with PD duration. Conclusions: Blood leukocytes mirror pathogenic mechanisms of PD, showing the systemic activation of the Nrf2 pathway and its link with synucleinopathy and clinical events. © 2019 International Parkinson and Movement Disorder Society